What Animates Place for Children? A Comparative Analysis. (18th November 2021) - Bodenhorn, Barbara; Lee, Elsa
Abstract : Drawing on comparative work in primary schools in East Anglia (United Kingdom), Oaxaca (Mexico), and the North Slope of Alaska (United States), we explore what children mean when they say places are "special" to them. Focusing on information gathered during walks designed and guided by these children, we examine the experiential, affective, communicative, and dynamic bases of relationality between children and their surroundings. We set out how effective curriculum design can productively incorporate such knowledge.